HIGHER-ORDER THINKING SKILLS ANALYSIS OF MADRASAH ALIYAH STUDENTS IN BIOLOGY LEARNING - Masru’ah; Siti Harnina Bintari; Siti Alimah (Madaris: Jurnal Guru Inovatif, 2021)
The challenges in the 21st century learning encourage educational institutions to produce young people who not only master in science but also have high-order thinking skills (HOTS). One way that can be taken to develop higher-order thinking skills is to provide HOTS-based exercises. Higher-order thinking skills are the ability to analyze, evaluate, and create information obtained to answer problems. The aim is to analyze the higher-order thinking skills of Madrasah Aliyah students in Pati regency on biology learning. This research is a type of quantitative research. The data was obtained by filling out the test instrument in multiple-choice form questions based on HOTS. Data collection was carried out by random sampling for XI and XII students majoring in Mathematics and Natural Sciences at Madrasah Aliyah in Pati Regency for the 2020/2021 academic year. Based on the results of data analysis, it can be concluded that the higher-order thinking skills of Madrasah Aliyah students in Pati Regency are in agood enough category. The results of this study are expected to be an illustration for education actors in Pati Regency, particularly for making improvements in the teaching and learning process.